Ethical Leadership and Artificial Intelligence Governance: Comparative Perspectives and Implications for Africa’s Development - Chukwudi, Celestina Ekene; Obadiah, Daniel Pastor; Okafor, Celestine Ogechukwu; Isaac, Grace Ugochi (Journal of Law & Policy Review, 2025)
The rise of Artificial Intelligence (AI) presents both transformative opportunities and significant ethical challenges for leadership and governance in Africa. This study examined ethical leadership and governance in the AI era, employing a comparative approach with a focus on Africa's development trajectory. Employing a documentary research Design and secondary sources of data, thematic Analysis was employed as the analytical technique. Thematic Analysis is among the most widely used qualitative data analysis techniques, providing a framework for identifying, analyzing, and interpreting meaning in datasets. The Analysis demonstrates that while AI has the potential to enhance public service delivery, governance effectiveness, and socioeconomic transformation, its use in African contexts is constrained by weak regulatory capability, fragmented governance frameworks, and insufficient ethical monitoring. A comparative analysis of global AI governance models reveals that institutional arrangements and leadership ideals are crucial in determining whether AI systems exacerbate inequality, bias, and democratic weaknesses or promote accountability, inclusivity, and public trust. The study recommended that African governments should invest in moral AI research and build regulatory sandboxes for controlled experimentation and policy development. Interdisciplinary advisory boards, including ethicists, technologists, and community representatives, should be institutionalised to guide AI governance.